Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (L'Harmattan, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie